Methods and Applications of Inversion - Hansen, Per Christian; Jacobsen, Bo Holm; Mosegaard, Klaus (Lecture Notes in Earth Sciences, 2000)
This collection of conference papers describes state-of-the-art methodologies and algorithms used in the treatment of inverse problems, focusing on seismology and image processing. The papers also describe new general methodologies for analysis and solution of inverse problems by means of statistical and deterministic algorithms. The book gives a glimpse of recent techniques, many of which are still under development